Obsessive-compulsive personality disorder increases cognitive inflexibility in people with coronary artery disease - Agne Stanyte; Naomi A. Fineberg; Julija Gecaite-Stonciene; Aurelija Podlipskyte; Julius Neverauskas; Alicja Juskiene; Vesta Steibliene; Nijole Kazukauskiene; Julius Burkauskas (Comprehensive Psychiatry)
Background: Cardiovascular diseases such as coronary artery disease (CAD) have a high prevalence of psychiatric comorbidities, that may impact clinically relevant outcomes (e.g., cognitive impairment and executive dysfunction). Obsessive-compulsive personality disorder (OCPD) is a common psychiatric comorbidity in CAD. It has a distinct cognitive profile characterised by inflexible thinking and executive dysfunction, which in turn may affect treatment adherence. However, the impact of OCPD on cognitive functioning in CAD is under-researched. We aimed to investigate the impact of OCPD on executive function in individuals with CAD undergoing rehabilitation, using cognitive tests relating to inflexibility and executive planning. Methods: Seventy-eight adults (median age 59 [53.0–66.0] years) with CAD were tested within three days of hospital admission for cardiac rehabilitation occurring within two weeks of experiencing an episode of unstable angina or myocardial infarction. The Compulsive Personality Assessment Scale (CPAS) was used to evaluate OCPD traits. Neurocognitive testing was performed using the Cambridge Automated Neuropsychological Test Battery (CANTAB) including tests of set shifting (Intra-Extra Dimensional [IED] Set Shifting), and executive planning (Stockings of Cambridge [SOC]). Results: Ten individuals with CAD fulfilled the operational criteria for DSM-5 OCPD. Individuals with comorbid OCPD made more IED intra-dimensional shift reversal errors (2.0 [2.0–4.0] vs. 1.0 [1.0–2.0], p = .004), reflecting a difficulty inhibiting previously learnt responses. When all participants were analysed as a group, negative associations were found between individual OCPD traits and other aspects of cognitive performance. Hoarding trait was associated with increased initial thinking time on the SOC at five moves (ρ = 0.242, p = .033), while the need for control and rigidity traits were each associated with increased initial thinking time on the SOC at two moves (respectively, ρ = 0.259, p = .022; ρ = 0.239, p = .035), reflecting slower executive planning. A preoccupation with details trait was associated with fewer errors on a compound discrimination stage of the IED (ρ = −0.251, p = .026). After controlling these correlations for gender and age, significant associations remained with hoarding (β = 0.243, p = .036), need for control (β = 0.341, p = .005) and rigidity (β = 0.259, p = .038) traits. Conclusions: Preliminary evidence suggests that individuals with CAD and comorbid OCPD traits show greater inflexibility than those without OCPD. Several OCPD traits were associated with slower planning, even after controlling them for age and gender. This may have implications for the success of rehabilitation.